Outcomes of a National Cohort of Children with Acute Severe Ulcerative Colitis - Akintimehin, Abisoye O.; O’Neill, Ríoghnach Sinead; Ring, Conor; Raftery, Tara; Hussey, Séamus (Frontiers in Pediatrics, 2018)
Aim: All Irish children with ulcerative colitis (UC) attend the National Centre for Paediatric Gastroenterology at Our Lady’s Children’s Hospital, Crumlin. The aim of this study was to determine the outcomes of children with acute severe ulcerative colitis and the impact of infliximab on these outcomes following its introduction for this indication in 2011. Methods: A retrospective chart review of all patients admitted with acute severe UC between January 1st 2009 and December 31st 2015 was undertaken. Patients were identified from the departmental database cross-referenced with the hospital inpatient enquiry system. Inpatients with a Paediatric Ulcerative Colitis Activity Index (PUCAI) of ≥ 65 were included. Data collected included baseline demographic and laboratory data, concomitant treatments, PUCAI scores on days 3 and 5, second-line treatments, surgery and discharge outcomes. Infliximab dose, frequency and available therapeutic drug monitoring results were recorded, along with clinical response outcomes (remission, primary and secondary loss of response). The cohort was sub-analysed to determine if there was any era effect pre- and post-introduction of infliximab (2009-2010 and 2011-2015 respectively). Results: Fifty-five patients (M:F=1.4:1) were treated for acute severe colitis over the study period (8 in the pre-infliximab and 47 in the post-infliximab era) and 46/55 (86%) had steroid refractory disease. Of these, 7/8(88%) required colectomy in the pre-infliximab era, compared with 15/47(36%) in the post infliximab era. The remission rate with second-line infliximab was 61% at maximal follow up. There were no identifiable factors that predicted likely success or failure of infliximab, including gender, CRP, day-3 and day-5 PUCAI scores. Of the 33 patients treated with infliximab, dose increase was required in 23/33(70%); 21/33(64%) received an accelerated dose schedule, and 9/33(27%) eventually needed colectomy. Primary and secondary loss of response to infliximab was seen in one and nine patients respectively. Conclusion: This is the first population-based study of the outcomes of severe UC in Irish children, and suggests a higher burden of steroid-refractory disease compared with previous international studies. While infliximab treatment has led to reduction in colectomy rates, a significant proportion of patients lose therapeutic effect.